Experiencing continuing education-experience of future urologists - Konopka, M.; Bellut, Laura; Beverungen, H.; Garcia, C. Cano; Dittmar, F.; Neutzer, M.; Siech, C. (Die Urologie, 2022)
Structured residency programmes within dedicated associations of hospitals, practices and medical care centres offer the opportunity to improve the quality of training and to increase the attractiveness of urology through fixed rotations of doctors in continued training. The implementation of such programmes is guided by the framework conditions of the respective location. Possible rotations range from andrology to paediatric urology and uro-gynaecology to interdisciplinary uro-oncology. An outpatient training period also offers the chance for a change of perspective and supports career orientation. Rotations in the interdisciplinary intermediate care unit offer the opportunity to become familiar with the care of complex disease processes, including the differential diagnostic assessment of abdominal diseases, which is important in urology. In summary, the diversity of urological training available can enable junior urologists to receive more individualised and targeted training by promoting multilayered, intersectoral as well as interprofessional training.
CRIS-Team WoS Importer:2022-08-19